Localised grey matter atrophy in multiple sclerosis is network-based: a coordinate-based meta-analysis. Issue 10 (October 2019) - Chiang, F.L.; Wang, Q.; Yu, F.F.; Romero, R.S.; Huang, S.Y.; Fox, P.M.; Tantiwongkosi, B.; Fox, P.T.
Abstract : AIM: To test the network degeneration hypothesis in multiple sclerosis (MS) with a two-stage coordinate-based meta-analysis by: (1) characterising regional selectivity of grey matter (GM) atrophy and (2) testing for functional connectivity involving these regions. MATERIALS AND METHODS: Meta-analytic sources included 33 journal articles (1, 666 MS patients and 1, 269 healthy controls) with coordinate-based results from voxel-based morphometry analysis demonstrating GM atrophy. Mass univariate and multivariate coordinate-based meta-analyses were performed to identify a convergent pattern of GM atrophy and determine inter-regional co-activation (as a surrogate of functional connectivity), with anatomical likelihood estimation and functional meta-analytic connectivity modelling, respectively. RESULTS: Localised GM atrophy was demonstrated in the thalamus, putamen, caudate, sensorimotor cortex, insula, superior temporal gyrus, and cingulate gyrus. This convergent pattern of atrophy displayed significant inter-regional functional co-activations. CONCLUSION: In MS, GM atrophy was regionally selective, and these regions were functionally connected. The meta-analytic model-based results of this study are intended to guide future development of quantitative neuroimaging markers for diagnosis, evaluating disease progression, and monitoring treatment response. Highlights: Localised grey matter atrophy in multiple sclerosis is clinically relevant. Coordinate-based meta-analysis determines consistent brain changes. Non-random regions of grey matter atrophy were functionally connected. Our results can guide future quantitative functional imaging marker development.